INFLUENCE OF RUTIN AND QUINIDINE ON ABSORBABLE SUTURES (Journal of Pharmaceutical Negative Results, 2022)
Suture materials play an important role in healing of wounds, enabling reconstruction and reassembly of tissue separated by a surgical procedure or a trauma, and at the same time facilitating and promoting healing and haemostasis [1]. The success of the surgical treatment is influenced by the proper closure and stabilization of surgical wound margins.Silk, is the one of the earliest sutures used for centuries,but it has some disadvantages of contamination. .Now-a-days, Vicryl suturing material is the commonly used material in oral surgery, because it does not allow adherence of plaque and is well suited for handling.In this study, two suture materials are compared based on their properties when coated with Rutin and Quindine.Material and Methods:Two absorbable sutures ( vicryl and pga) were taken. The extraction of reserpine and rutin was done. Both the extracts were kept in two test tubes separately. The sample was sent to scanning electron microscopy, tensile strength ie.mechanical testing, degradation of ph 7.2 and ph 4.4, anti inflammatory and antioxidant activity was done. The results were placed in excel sheets and graphs were obtained.Results and discussion: Absorbable sutures are ideal for internal and deep wounds and generally one of them loses most of its tensile strength in 1 to 3 weeks and is fully absorbed within 3 months. In this study Vicryl and PGA was used and which was incorporated into rutin and reserpin. Vicryl and PGA sutures have shorter and longer-term stability.however, may be used for longer-term applications of wound closure, tendon repair and arthroplastyConclusion: The study demonstrated that the PGA were stronger and had greater tensile strength than the Vicryl. Rutin shows better anti inflammatory action and antioxidant property than Quinidine.